Pengaruh Kualitas Kehidupan Kerja, dan Motivasi Intrinsik terhadap Komitmen Afektif dengan Kepuasan Kerja sebagai Pemediasi - Widya Karanita; Ignatius Soni Kurniawan (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This study aims to analyze the effect of quality of work life and intrinsic motivation on affective commitment with job satisfaction as a mediating variable on the employees of Dinas Perhubungan Kabupaten Bantul. This type of research is quantitative research. The sample size of this study was 92 employees. The sampling technique used the accidental sampling method. The data collection method in this study used a questionnaire. The data analysis technique used multiple linear regression analysis and Sobel test. The results showed that the quality of work life had a significant effect on job satisfaction. Intrinsic motivation has no significant effect on job satisfaction. Quality of work life has a significant effect on affective commitment. Intrinsic motivation and job satisfaction have no significant effect on affective commitment. Job satisfaction does not mediate the effect of quality of work life and intrinsic motivation on affective commitment. Keywords: Affective Commitment; Intrinsic Motivation; Job Satisfaction; Quality of Work Life.